MEMBANGUN GREEN ECONOMY: STRATEGI MENUJU DUNIA YANG LEBIH HIJAU - Firdaus; Niti Lestari; Herlina Lusiana; Purboyo; Mursanto; Andi Zulfikar Darussalam (EDU RESEARCH, 2025)
The transition to a Green Economy has become a crucial strategy in addressing environmental challenges while ensuring sustainable economic growth. This article explores various approaches and strategies that can be implemented to build a more environmentally friendly economic system. Key aspects include the adoption of renewable energy, sustainable resource management, eco-friendly business practices, and government policies that support green initiatives. By integrating sustainability principles into economic development, businesses and policymakers can contribute to a more resilient and equitable future. The discussion also highlights the role of technology, innovation, and community participation in accelerating the shift toward a greener economy.